Tripleglow / Nazia Zulaiqha Nor Azlan … [et al.]. - Nor Azlan, Nazia Zulaiqha; Balqis, Nurain; Mohd Sharil, Huda Farzana; Erwan, Nur Amirah Athilah; Ismail, Nur Kiasatina Amirah; Zakaria, Nur Aina Amirah (2024)
Brief description of the business and product concepts. TripleGlow is a revolutionary 3-in-1 skincare brand dedicated to simplifying beauty routines without compromising effectiveness. At its core, TripleGlow offers a comprehensive skincare solution that combines toner, moisturizer and sunscreen into a single, seamless product. Infused with potent natural ingredients and cutting-edge technology, the product aims to streamline daily skincare rituals, catering to individuals seeking a hassle-free yet high-quality approach to skincare. By harnessing the power of three crucial steps in one easy-to-use formula, TripleGlow seeks to empower users with radiant, healthier-looking skin while saving time and effort in their daily routine skincare. The product's innovative formulation incorporates the vital functions of toning to balance the skin's pH, moisturizer to hydrate and nourish, and sunscreen to shield against harmful UV rays. Infused with potent natural ingredients and cutting-edge technology, TripleGlow’s all-in-one formula not only simplifies daily routines but also delivers exceptional results. The product offers users a time-saving yet incredibly effective approach to achieving radiant, healthier skin. Through its innovation and dedication to simplifying beauty rituals, TripleGlow seeks to empower individuals with a streamlined, luxurious, and transformative skincare experience. The target market and projections: TripleGlow 3-in-1 skincare, which includes toner, moisturizer, and sunscreen functions, is aimed at a varied market looking for a more simplified and efficient approach to skincare. With a focus on those who lead busy lives, this product appeals to those who value a simpler skincare routine without sacrificing quality. The young individuals, students, and those with busy lives who appreciate time-saving solutions and versatile items are among the target demographics. TripleGlow's toner helps to balance the pH of the skin, preparing it for following skincare stages, while the moisturizer deeply hydrates, providing a smooth and nourished face. Sunscreen provides an important layer of protection against dangerous UV rays, making it particularly appealing to health-conscious customers.